Design and CFD analyses of aluminium alloy-based vortex tubes with multiple inlet nozzles for their optimum performances in sustainable applications. (2021) - Jee Kanu, Nand; Ashok Patil, Sanjay; Sutar, Venkateshwara; Gupta, Eva; Kumar Singh, Gyanendra; Kumar Vates, Umesh; Chavan, Sachin
Abstract: The vortex tube is a radical instrument described for discretizing the compressed gas/fluid into cold and hot streams. The pressurized gas/fluid is injected tangentially in the swirl chamber of the vortex tube and it is expanded with a high rate of rotation. The cone-shaped spout on the end of the tube permits the compressed gas/fluid to flee out. The rest of the gas/fluid is compelled to return to an internal portion of the vortex tube of diminished diameter inside the external vortex. The present research is done on three-dimensional flow using computational fluid dynamics (CFD) method on aluminium alloy-based vortex tubes with 1, 2, 3, and 4 nozzles at various angles such as 0°, 90°, 180° and 270°, respectively. The material used in the present investigation is aluminium alloy. The focus is to determine the aluminium alloy-based vortex tube that provides an optimal performance over the conventional tubes with a maximum temperature drop. To that, the temperature at the hot end of the vortex tube is kept within the permissible limit to minimize its contribution to the global warming.